Cell-Derived Extracellular Matrix for Tissue Engineering and Regenerative Medicine - Assunção, Marisa; Dehghan-Baniani, Dorsa; Yiu, Chi Him Kendrick; Später, Thomas; Beyer, Sebastian; Blocki, Anna (Frontiers in Bioengineering and Biotechnology, 2020)
Cell-derived extracellular matrices (CD-ECMs) captured increasing attention since the first studies in the 1980s. The biological resemblance of CD-ECMs to their in vivo counterparts and natural complexity provide it with a prevailing bioactivity. CD-ECMs offer the opportunity to produce microenvironments with costumizable biological and biophysical properties in a controlled setting. As a result, CD-ECMs can improve cellular functions such as stemness or be employed as a platform to study cellular niches in health and disease. Either on their own or integrated with other materials, CD-ECMs can also be utilized as biomaterials to engineer tissues de novo or facilitate endogenous healing and regeneration. This review provides an overview over the methodologies used to facilitate CD-ECM deposition and manufacturing. It explores the versatile uses of CD-ECM in fundamental research and therapeutic approaches, while highlighting innovative strategies. Further, current challenges are identified and it is accentuated that advancements in methodologies, as well as innovative interdisciplinary approaches are needed to take CD-ECM-based research to the next level.